2011
DOI: 10.1002/etc.708
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of nano‐zinc oxide in environmentally and biologically important matrices

Abstract: Increasing manufacture and use of engineered nanoparticles (NPs) is leading to a greater probability for release of ENPs into the environment and exposure to organisms. In particular, zinc oxide (ZnO) is toxic, although it is unclear whether this toxicity is due to the zinc oxide nanoparticles (ZnO), dissolution to Zn2+, or some combination thereof. The goal of this study was to determine the relative solubilites of both commercially available and in-house synthesized ZnO in matrices used for environmental fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
173
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(190 citation statements)
references
References 38 publications
15
173
0
2
Order By: Relevance
“…Surface charge and aggregation tend to vary with pH, where the further the environmental pH is from the ENM's PzC, the farther the surface charge is from zero. This increases their stability, since like charges will repel Judy et al 2011;Reed et al 2012;Wang et al 2011). However, high IS can minimize the forces keeping NPs separate and cause aggregation and sedimentation (French et al 2009;Handy et al 2008) even for a pH that is far from the PzC.…”
Section: Aggregation In Watermentioning
confidence: 99%
See 2 more Smart Citations
“…Surface charge and aggregation tend to vary with pH, where the further the environmental pH is from the ENM's PzC, the farther the surface charge is from zero. This increases their stability, since like charges will repel Judy et al 2011;Reed et al 2012;Wang et al 2011). However, high IS can minimize the forces keeping NPs separate and cause aggregation and sedimentation (French et al 2009;Handy et al 2008) even for a pH that is far from the PzC.…”
Section: Aggregation In Watermentioning
confidence: 99%
“…Conversely, the zeta potential for TiO 2 at 10 mM CaCl 2 is close to zero at pH 7 (Petosa et al 2012). The zeta potential for ZnO seems to vary significantly from very positive to very negative at pH values ranging from 4 to 10 (Jiang et al 2009a, b;Petosa et al 2012;Reed et al 2012). The zeta potentials for Au and Cu/CuO tend to be close to zero for a pH between 5.5 and 8.5, except in groundwater for Au and in algal growth media for Cu/CuO (Griffitt et al 2008;Hitchman et al 2013;Judy et al 2011;Wang et al 2011).…”
Section: Aggregation In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…22,27,28 In order to assess whether the effect induced by ZnO Nps on Jurkat cells was due to the Np itself or to the Zn 2+ ions released by the particles, the cells were exposed to ZnCl 2 salt at three different concentrations (1, 10, and 100 µg/mL Zn 2+ ) and the MAPK and NFκB activation was assessed in Western blots.…”
Section: Effect Of Zn 2+ Ions On the Activation Pathway Induced By Znmentioning
confidence: 99%
“…For example, titanium dioxide nanoparticles (nano-TiO 2 ) were assumed to be practically insoluble in freshwater in many studies, [8], [9] while they were confirmed being able to dissolve in acid aqueous NaCl solutions (pH < 3) at temperatures of 25 and 37 ℃. [10] Dissolution of zinc oxide nanoparticles (nano-ZnO) was observed with 7.18-7.40 mg/L dissolved Zn in pure water, but with much higher dissolved Zn concentration (> 34 mg/L) in a cell culture medium [11].…”
Section: Introductionmentioning
confidence: 99%